A critical analysis of melanoma malpractice litigation: Should we biopsy everything?. (2nd August 2016) - Rayess, Hani M.; Gupta, Amar; Svider, Peter F.; Raza, S. Naweed; Shkoukani, Mahdi; Zuliani, Giancarlo F.; Carron, Michael A.
Abstract : Objectives/Hypothesis: The aim of this study was to evaluate factors raised in malpractice litigation related to the diagnosis and management of melanoma and to further assess issues impacting outcome. Study Design: Retrospective chart review. Methods: The Westlaw legal database was searched for malpractice litigation resolved over the last 20 years relating to melanoma. Cases were evaluated for allegations, defendant specialty, outcome, and other issues raised. Results: Of the 80 cases evaluated, 49% were resolved in the defendants' favor. In greater than 80% of cases, there was alleged misdiagnosis. In 35% of cases, the patient had expired secondary to melanoma at the time of litigation. There was no statistical difference in payments upon comparison of cases with and without mortality. A greater proportion of cases with dermatologists and pathologists as defendants involved alleged misdiagnosis. The most common locations for melanoma were the extremities and the head‐and‐neck region, at 32.5% and 22.5%, respectively. Location did not significantly impact the outcome of cases. Conclusion: Malpractice litigation relating to melanoma involves numerous physicians, including dermatologists, pathologists, and otolaryngologists. Alleged misdiagnosis of a pigmented lesion was the most common cause of litigation and involved physicians from numerous specialties. Patients who were misdiagnosed had a significantly higher likelihood of having active disease at the time of litigation. Ultimately improved methods of detecting concerning pigmented lesions need to be developed. Factors such as death and poor cosmetic outcome did not significantly impact litigation outcome. Level of Evidence: NA Laryngoscope, 127:134–139, 2017